Global Foreign Direct Investment: A network perspective. Issue 4 (August 2019) - Bolívar, Luis Miguel; Casanueva, Cristóbal; Castro, Ignacio
Highlights: Country features influence both the network structure and the node's power position. The FDI network structure responds to homophilic relations among developed countries. The FDI network has a core–periphery structure with few economies comprising the core. The FDI network is not influenced by the Bilateral Investment Treaties network. Connections to powerful partners may provide benefits to countries' trade performance. Abstract: Foreign Direct Investment (FDI) research has usually focused on inward and outward levels of assets flows and stocks, yet very few studies have examined the Global FDI Network. We study the economic performance of countries in terms of their associations with certain FDI partners employing social network analysis. This new approach shifts the focus away from the study of certain country features and their influence on FDI stock levels. Our study of FDI stocks from 229 economies sheds light on the interactions of the global FDI network within its singular context of country-level determinants, its after-effects, internal patterns, and relationship with the network of Bilateral Investment Treaties (BITs). Our conclusion is that country features such as size, openness, skill levels, and institutional stability not only set the pace of FDI, but that they also influence both the network structure and the power positions of each node. We investigate whether that structure responds to homophilic relations between countries or to core–periphery patterns with only a few core economies and we question the strategy of signing BITs to form FDI relations. Finally, we inquire into strategic connections with powerful partners, to ascertain whether they provide beneficial settings for country growth and trade performance.